2023
DOI: 10.1126/sciadv.ade8513
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-embedded stretchable nanoelectronics reveal endothelial cell–mediated electrical maturation of human 3D cardiac microtissues

Abstract: Clinical translation of stem cell therapies for heart disease requires electrical integration of transplanted cardiomyocytes. Generation of electrically matured human induced pluripotent stem cell–derived cardiomyocytes (hiPSC-CMs) is critical for electrical integration. Here, we found that hiPSC-derived endothelial cells (hiPSC-ECs) promoted the expression of selected maturation markers in hiPSC-CMs. Using tissue-embedded stretchable mesh nanoelectronics, we achieved a long-term stable map of human three-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…Our approach may better mimic natural tissue morphogenesis, where multiple cell fates emerge simultaneously from a uniform cell population. Studies have also shown that supporting cells, such as endothelial cells, improve the maturation of human induced pluripotent stem cellderived cardiomyocytes 59,60 , and that co-differentiation of different lineages concurrently more closely recapitulate the conditions occurring during embryonic development 61 . An interesting hypothesis to explore with our technology is whether co-differentiation of supporting cells (e.g., endothelial cells) adjacent to parenchymal cells (e.g., muscle cells) has additional benefits for phenotypic maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach may better mimic natural tissue morphogenesis, where multiple cell fates emerge simultaneously from a uniform cell population. Studies have also shown that supporting cells, such as endothelial cells, improve the maturation of human induced pluripotent stem cellderived cardiomyocytes 59,60 , and that co-differentiation of different lineages concurrently more closely recapitulate the conditions occurring during embryonic development 61 . An interesting hypothesis to explore with our technology is whether co-differentiation of supporting cells (e.g., endothelial cells) adjacent to parenchymal cells (e.g., muscle cells) has additional benefits for phenotypic maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Co-culture of CMs with endothelial cells has also been shown to improve expression of cardiac maturation markers, including Cx43, TNNI3, Kir2.1, and CD36, with a 3 : 1 CM : EC ratio being most favorable. 226 Moreover, this ratio showed improved electrophysiological characteristics and sarcomere organization. While 4 genetically distinct subtypes of CM were identified when hiPSC-CMs were cultured alone, hiPSC-CMs cultured with ECs showed an additional subtype that upregulated genes associated with metabolism and cardiac muscle contraction.…”
Section: Applications Of Heart-on-a-chip Technologiesmentioning
confidence: 95%
“…Given that CMs comprise only 30% by number of total cells in the heart, co-culture with other cell types, such as fibroblasts, neural cells, endothelial cells, and immune cells has been shown to promote maturation through intercellular interaction and paracrine signaling. 8,[212][213][214][215][216][217][218][219][220][221][222][223][224][225][226] Co-culture of hESC-CMs with human cardiac fibroblasts (at an optimized 4 : 1 ratio) in a microfluidic chip containing an array of microposts was found to improve tissue maturity and anisotropy after just 2 weeks (Fig. 3c).…”
Section: Controlmentioning
confidence: 99%
“…The heart is one of the most vascularized organs in the body, with an equivalent number of cardiomyocytes and endothelial cells present in the myocardium 57 . Its complex vasculature both maintains heart homeostasis and promotes cardiac maturation under healthy conditions 157 . Moreover, endothelial cells serve as a physical and chemical barrier in the heart, indicating that direct administration of viruses or drugs to the engineered heart tissue may lead to an overestimation of their effects.…”
Section: Future Directionsmentioning
confidence: 99%
“… 57 Its complex vasculature both maintains heart homeostasis and promotes cardiac maturation under healthy conditions. 157 Moreover, endothelial cells serve as a physical and chemical barrier in the heart, indicating that direct administration of viruses or drugs to the engineered heart tissue may lead to an overestimation of their effects. In parallel, the immunomodulatory effects of endothelial cells and immune cells have been implicated in many heart dysfunctions.…”
Section: Future Directionsmentioning
confidence: 99%